2020
DOI: 10.26434/chemrxiv.12159207
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An NADH-Inspired Redox Mediator Strategy to Promote Second-Sphere Electron and Proton Transfer for Cooperative Electrochemical CO2 Reduction Catalyzed by Iron Porphyrin

Abstract: We present a bioinspired strategy for enhancing electrochemical carbon dioxide reduction catalysis by cooperative use of base-metal molecular catalysts with intermolecular second-sphere redox mediators that facilitate both electron and proton transfer. Functional synthetic mimics of the biological redox cofactor NADH, which are electrochemically stable and are capable of mediating both electron and proton transfer, can enhance the activity of an iron porphyrin catalyst for electrochemical reduction of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…25,26 Smith et al reported the first homogeneous co-electrocatalytic system for the reduction of CO 2 using a NADH analogue as the RM and an Fe tetraarylporphyrin complex that shows enhanced catalytic activity as a combined system. 27 The NADH analogue transfers protons and electrons during the reaction, although the exact reaction sequence is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Smith et al reported the first homogeneous co-electrocatalytic system for the reduction of CO 2 using a NADH analogue as the RM and an Fe tetraarylporphyrin complex that shows enhanced catalytic activity as a combined system. 27 The NADH analogue transfers protons and electrons during the reaction, although the exact reaction sequence is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[40][41][42][43] Indeed, the suppression of metal-centered reduction can limit the formation of offpathway metal hydride intermediates necessary for hydrogen evolution 35,44 and thereby favor CO2 reduction catalysis. As part of a larger program in electrocatalysis via bioinorganic mimicry, 6,24,25,[45][46][47][48] our synthetic approach was inspired by mononuclear iron hydrogenase enzymes, which catalyze the reduction of methenyl-H4MPT + to methylene-H4MPT in methanogenic archaea. 49 In these systems, heterolysis of H2 and hydride shuttling is enabled by a single redox-innocent iron(II) site that synergistically interacts with a redox non-innocent guanyl pyridinol cofactor in the primary coordination sphere to provide reducing equivalents (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…16 Smith et al reported the first homogeneous co-electrocatalytic system for the reduction of CO2 using a NADH analogue as the RM and an Fe tetraarylporphyrin complex that shows enhanced catalytic activity as a combined system. 17 The NADH analogue transfers protons and electrons during the reaction, although the exact reaction sequence is currently unknown.…”
Section: Introductionmentioning
confidence: 99%